Fabrication of a Porous Metal-Organic Framework with Polar Channels for 5-Fu Delivery and Inhibiting Human Osteosarcoma Cells - Li-Chun Zhao; Mei Tang; Qian-Hua Zhang; Zhi-Yi Hu; Hong-Wei Gao; Xia-Yun Liao; Gang Wang; Jing Leng (Journal of Chemistry)
As an emerging kind of crystalline material, the metal-organic framework (MOF) has shown great promise in the biomedical domains such as drug storage and delivery. In this study, a new porous MOF, [[Dy2(H2O)3(SDBA)3](DMA)6] (1, H2SDBA = 4,4′-sulfonyldibenzoic acid, DMA = N,N-dimethylacetamide (C4H9NO)), with uncoordinated O donor sites has been fabricated using a bent polycarboxylic acid organic linker under the solvothermal condition. The structure of the obtained crystalline product has been fully determined by the X-ray single-crystal diffraction, TGA, elemental analysis, XRD, and the gas sorption measurement. Due to the suitable window size and polar atom functionalized 1D channels, the activated 1 (1a) compound was used for the anticancer drug 5-fluorouracil (5-Fu, C4H3FN2O2) loading by a simple impregnation method. A moderate drug loading and pH-dependent drug-release behavior could be observed for 1a. Furthermore, as indicated by the MTT assay, this drug/MOF composite shows low toxicity toward the human normal cells and demonstrates obvious anticancer activity against the human osteosarcoma cell line MG63.